Podmiotowość zwierząt w świetle dwóch koncepcji umowy społecznej - Jankowski, Wojciech (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The status of an animal in Polish law is not clear, but certainly we cannot speak about legal subjectivity of animals. Art. 1 of the Animal Protection Act introduces the concept of legal dereification, but we are not dealing with an “animal rights”, but with the legal protection ofanimals. It means that there are obligations imposed on humans that determine their behavior towards animals, but it does not mean that the animals have rights. More and more votes, also among lawyers, propose to change the current legal situation by giving animals subjectivity. However, considering this issue from the perspective of the relationship between law and morality, it seems that the discussion should be preceded by a theoretical reflection and reflection on the subjectivity of animals in a broader sense. In the justification to the judgment of the Constitutional Tribunal of 10 December 2014 on the ban on ritual slaughter, we find a statement that “in the near future, there will be grounds for analyzing human behavior towards animals in the context of the premise of morality”. The aim of this article is to conduct an analysis made from the perspective of the concept of a social contract. Article analyzes compatibilistic attempts to justify animal subjectivity on the basis of the contract theory. Firstly, Mark Rowlands’ concept will be discussed, which is one of the best-known attempts to create a theory of animal rights based on the concepts of social contract. According to Rowlands, it is possible to include animals in the circle of moral subjects from the perspective of John Rawls’ contract theory.
Keywords: animal rights; philosophy of law; contractualism; Rawls, John